Supreme efficacy: The ultrahigh performance of ZnO adsorbent for ambient-temperature H2S removal in integrated H2S–N2 gas - Gunawan, Melia L.; Muntaqin, Althafa; Saraswati, Made A.; Nurdini, Nadya; Subagjo; Kadja, Grandprix T.M.; Rasrendra, Carolus B. (Case studies in chemical and environmental engineering, 2024)
Herein, Na2CO3 emerges as a superior precipitating agent for synthesizing ZnO adsorbent, demonstrating remarkable structural properties that dramatically enhance the H2S removal. ZnO precipitated by Na2CO3 (ZnO-SC) exhibits the highest breakthrough capacity at a space velocity of 25,000 h⁻1, reaching a capacity of 32.1 mg S g−1 adsorbent, while that precipitated by NH4OH (ZnO-AH) and the commercial adsorbent (ZnO-Com) achieve capacities of 2.4 mg S g−1 adsorbent and 7.1 mg S g−1 adsorbent, respectively. Moreover, kinetic studies on the adsorbent deactivation have been conducted to obtain insights into the adsorbent behavior and provide the fundamental basis for further improvement. [Display omitted]